Visualizing partially loosened fastener through frequency-wavenumber analysis of ultrasonic wavefield - Lee, Shi Yn; Chia, Chen Ciang; Romli, Fairuz Izzuddin; Mazlan, Norkhairunnisa; Lee, Jung-Ryul; Harmin, Mohammad Yazdi (The Aeronautical and Astronautical Society of the Republic of China, 2024)
Aerospace thin-walled structures and alike are susceptible to various damages and flaws, including the loosening of fasteners, that must be non-destructively evaluated and repaired to avoid catastrophic failure. Guided ultrasonic wavefield has great potential to evaluate loosened fasteners, but state-of-the-art result processing methods are either not supporting direct visualisation of a loosened fastener or are unable to quantify the level of loosening. In this work, a more detailed analysis of the wavefield data was experimentally conducted in the frequency and wavenumber domains using wavenumber highpass and bandpass filters, as well as the wavenumber imaging algorithm. Six fasteners fixed at a simple aluminium plate were inspected, among which one was deliberately loosened from the nominal 100 lb-in to a few discrete levels to simulate a flaw. The imaging results revealed that a fastener loosened to 0, 20, 40, and 60 lb-in, respectively, could be distinctively visualised but marginally discernible when loosened to 80 lb-in. Further work is being conducted to improve the detection sensitivity and properly quantify the results.